Effects of high rate of alachlor and metolachlor on microbial activities in soil - Sahid, Ismail (Universiti Putra Malaysia Press, 1994)
A study was carried out to investigate the effects of the two acetanilide herbicides alachlor and metolachlor on microbial activities in sandy loam soil. Effects of the herbicides on CO2 evolution were monitored for 50 d in ambient conditions. The results showed that alachlor and metolachlor generally caused an initial decrease in CO2 release, which subsequently increased to control level after 25 d of incubation. Both herbicides exert less effect on CO2 evolution at lower concentrations. Fungal and bacterial populations in the soil also declined in the presence of either herbicide at higher concentrations. Phosphatase activity was generally affected in the presence of either herbicide except in soil treated with metolachlor at 20 ppm.